TEACHERS AS DETERMINANTS OF SUCCESS IN EDUCATION REFORM - Sri Mulyani Nasution; Kristo Paulus; Darin Brenda Iskarina (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
Modernity encourages students to have multidimensional and high-quality competencies to be able to face and overcome the consequences of developments and changes that are taking place globally in the context of modernization. To achieve this need, the teacher also becomes a determinant of educational success. Unfortunately, the ever-increasing need for the teacher's role is not followed by fulfilling the teacher's competence needs. The main task of the teacher to develop students’ talents and interests seems to be not optimally implemented. From these problems, it is concluded that: (1) Teachers have an important role in the success of education reform; (2) The teacher has a central task as a leader in the learning process in class; (3) Success in learning can be seen from the outcomes of students; (4) The learning that is carried out must be able to have an impact on change, especially for students. (5) For education reform to run optimally, teachers must function as contained in PP 19 of 2017 concerning Teachers.